2017
DOI: 10.1002/hep.29018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the sterol regulatory element‐binding protein pathway suppresses hepatocellular carcinoma by repressing inflammation in mice

Abstract: Inhibition of de novo lipid biosynthesis by suppressing the SREBP pathway prevents HCC. This study identifies a previously underappreciated role of the SREBP pathway in HCC and suggests a novel metabolic strategy to control liver cancer. (Hepatology 2017;65:1936-1947).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 41 publications
5
45
0
Order By: Relevance
“…24 Recent study reported that inhibition of de novo lipid biosynthesis by suppressing the SREBP pathway prevented HCC progression. 37 Our present data also confirmed that decreased TIP30 could promote HCC cell growth via SREBP1-related lipid metabolism in vitro and in vivo , which was also responsible for elevated FASN and SCD expression induced by TIP30 deficiency.…”
Section: Discussionsupporting
confidence: 85%
“…24 Recent study reported that inhibition of de novo lipid biosynthesis by suppressing the SREBP pathway prevented HCC progression. 37 Our present data also confirmed that decreased TIP30 could promote HCC cell growth via SREBP1-related lipid metabolism in vitro and in vivo , which was also responsible for elevated FASN and SCD expression induced by TIP30 deficiency.…”
Section: Discussionsupporting
confidence: 85%
“…As a consequence, cholesterol depletion or trafficking blockade hinders tumour growth and invasion in a variety of cancers [24][25][26][27] .…”
Section: Nature Metabolismmentioning
confidence: 99%
“…Furthermore, genetic depletion or pharmacological inhibition of SREBP1 has been shown to suppress the epidermal growth factor receptor (EGFR)-induced glioblastoma (12). Blocking SREBP pathway prevents hepatocellular carcinoma (HCC) in mouse models (13). Thus, SREBP1 is required to support proliferation in some cancer cells.…”
mentioning
confidence: 99%